Mentoring and its Effects on Turnover Intensions in Perspective of Pakistan’s Telecom Sector - Hussain, Syed Saad; ., Ahsan Raza Jaffari; ., Muhammad Wasiq Ejaz; ., Asad Khattak; ., Kashif Ur Rehman; Muhammad Aslam Khan (Information Management and Business Review, 2011)
In today’s era of towering competition the retention of workforce is highly desirable for long term success of any organization. The employees serve as backbone for any organization and are responsible for attaining the laid down objectives of the organization. The ongoing study investigates the effects of mentoring on turnover intensions of employees working in telecom sector of Pakistan. Researchers retrieved data with the help of questionnaires based on five point likert scale from almost 300 employees working in telecom organizations of Pakistan. Multiple regressions were used to analyze the collected data. Result shows that mentoring mostly is negatively associated with turnover intension because employee was not satisfied with mentoring and commitment in employees is only due to experienced learning which helps to develop additional skills in employee.